Liquid stream instability under an acoustic field - Tay, Jihui (Nanyang Technological University, 2021)
The Plateau-Rayleigh instability theory provide a good explanation behind the breakup of liquid streams. An experimental study on the liquid stream instability under a controllable acoustic field was conducted in this study. Parameters like breakup length of the stream, aspect ratio of droplets and viscosity of the fluids were investigated under a standing wave of different frequencies, acoustic power and flowrates. Results that were obtained from liquid stream under the acoustic field were compared to those without. It would give us a general understanding on the breakup of the stream. Under ambient conditions, water stream with a flowrate equal to and higher than 6ml/min would not breakup. For silicone oils with viscosity 5cSt, 10cSt and 20cSt, breakup in ambient condition happened only at 2ml/min. However, the introduction of an acoustic field allowed breakup to occur across all the flowrates. The breakup were in the first-wind and second-wind induced regime. It also reduced the breakup length at lower flowrates. Dimensionless numbers like Reynolds number, Ohnesorge number and Weber number would help to explain other phenomenon that occurred during the experiments like the effects of surface tension and viscosity. The Reynolds number can help to predict the type of flow – laminar or turbulent. Knowing the Reynolds number, the dominant forces that are affecting the breakup can be deduced. With an Ohnesorge number less than 0.1, multiple satellite droplets would form while a number higher than 0.1 would prevent the stream from breaking up due to the viscous forces. However, with a relative high Weber number, the Ohnesorge number effects would not be as significant. However, under the effects of an acoustic field, the results found were different. Breakup occurred with Ohnesorge number higher than 0.1 even though the Weber number was very small. Breakup also occurred in the first and second-wind induced regime which should have been in the Rayleigh regime without an acoustic field. This result suggested the effects of an acoustic field had an impact on the stream.